WALISONGO SEBAGAI FAKTA SEJARAH ISLAM NUSANTARA - Akhmad, Fandi (Al-Munqidz : Jurnal Kajian Keislaman, 2020)
Preaching is the duty of every Muslim in accordance with the words of the Prophet Muhammad, "Ballighu‘ anni though ayatan "which means to convey what comes from me even though one verse. That is why, no matter whether Muslims are traders, artisans, farmers, fishermen and so on, they have the primary obligation to convey the truth of Islam to anyone and anywhere.The teachings of Islam began to develop very rapidly and were accepted by the community because its teachings were easy to understand and very easy to understand. Certainly not a very easy thing, the spread of Islam through trade, education and culture requires a long time to be accepted in society.For the Indonesian Muslim community, the name walisongo has a special meaning which is then connected with the presence of sacred figures in Java, who played an important role in the spread and development of Islam in the 15th and 16th centuries AD.The existence of the Wali Songo figure as a spiritual teacher who is loaded with mystical matters, which is covered by an adidunia, is more prioritized than anything else because the Da'wah concept applied by Wali Songo prioritizes the teachings of Sufism.His story is quite interesting and alluring and a lot of lessons learned in the struggle for the Islamic religion. As well as being a matter of pride. Its presence is able to be accepted by the people from the king to the middle to lower classes.